Forward Chaining: Metode untuk Mengembangkan Sistem Prediksi Penyakit Gigi dan Mulut - Bobby Anggara Azhari; Neni Mulyani; Andy Sapta (Universitas Hamzanwadi, 2022)
Handling dental and oral diseases require knowledge, techniques, and experts so that the disease can be handled properly. However, the lack of a team of experts and the lack of public knowledge about this disease, a system is needed that can prevent and overcome the symptoms of the disease. This study aims to apply forward chaining as a method to develop a prediction system for dental and oral diseases. The method used in this study is forward chaining and the model used is the waterfall with stages of analysis, system design, application, integration testing, operation maintenance. This study carried out data processing from the clinic. The data is then processed data. Based on the results of black box testing involving patients, and the community directly, the function in this system is already Use of this system can provide convenience for the community, and patients in diagnosing dental and oral diseases.